Pelatihan Peningkatan Kualitas Artikel Ilmiah Nasional Bagi Guru SMA - Mesran Mesran; Suginam Suginam; Trans Ningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Training carried out to improve the quality and quality of scientific articles for school teachers is very important because a scientific article is an idea or a solution to solving a problem, the importance of scientific research is to improve the quality of thinking of future researchers, the problem that often occurs is that there are still many authors of scientific articles especially from among teachers who are still messy, not according to the writing scheme and even writing bibliography which is still manual, this has an impact on teachers' difficulties in carrying out scientific publications in places that have a high reputation such as accredited national journals and international journals. This made the authors pay attention to providing training in the use of Mendeley to teachers with the aim of providing convenience in writing scientific articles, making bibliography, searching related scientific articles to improve the quality of writing scientific articles, the number of teachers in training was 35 people. The result of this activity is that the teacher's ability to use Mendeley is increasing, especially in making references or bibliography, the process of evaluating lecturers' understanding is carried out by giving a questionnaire to 6 questions to teachers who have attended training on using Medeley on downloading application knowledge and linking the Mendeley application with word is very helpful for understanding teachers well, the service that is carried out goes well with satisfying results